Precocious and Early Central Puberty in Children With Pre-existing Medical Conditions: A Single Center Study - Winter, Sarah; Durand, Adélaïde; Brauner, Raja (Frontiers in Pediatrics, 2019)
Background: Early puberty is a reported finding in children with pre-existing medical conditions. Data pertaining to such situations are limited. Methods: A retrospective, single-center study was conducted on children with early puberty (onset before the age of 10 years in girls and 11 years in boys) diagnosed on the background of a known pre-existing medical condition. Results: Early puberty was diagnosed in 25 patients. Mean age at puberty was 6.65 ± 2.3 years in girls (n=15) and 9.4 ± 0.84 years in boys (n=10). The most common disorders were psychomotor delay (n=12), psychiatric disorders (n=7) and/or epilepsy (n=5). Early puberty was among the symptoms experienced by patients with a variety of syndromes including lipofuscinosis (2 siblings), Dravet syndrome and Silver-Russel Syndrome. Pituitary stalk interruption with agenesis of olfactory bulbs and optic nerve atrophy was found on imaging in one patient who presented with epilepsy and autism spectrum disorder. Karyotype analysis revealed chromosomal duplication (chromosome 15 in 2 cases; chromosomes 17 and 11 in one case each) in 4 of 8 patients evaluated. Conclusions: Data from patients with complex disease who experience early puberty may provide clues regarding the genetic determinants of pubertal development.